Terminal battery status information based fairness-aware SWIPT strategy - Zhirui HU (Tongxin xuebao)
To solve the battery depletion problem,the terminals’ battery status information (BSI) was proposed to be taken into consideration in simultaneous wireless information and power transfer (SWIPT) strategies,and a SWIPT strategy to guarantee the rate fairness was provided.BSI determined the terminals’ sufferable received rate and harvested energy.The proposed scheme was formulated as an optimization problem to max-min user rate,with rate/energy requirement constraints and the sufferable rate/energy constraints.To solve optimization problem,the receivers were firstly classified with their battery level,then the optimal solutions were obtained by the proposed iteration optimization-based algorithm.With the proposed scheme,the transmit power and the power splitting factor would be controlled and the data rate at receivers,especially the receivers that with lower battery level would be restricted,avoiding the required battery consumption to exceed battery level.Simulation results reveal that the proposed scheme can prolong battery lifetime and avoid the battery depletion problem,and its fairness performance is strengthened with the difference decreasing among the receivers’ battery level.